Energy Analysis of Cavitation Bubbles Under Dual-Frequency Acoustic Excitation - LV, Liang; HU, Kai; LIU, Fei; LI, Yawei; CUI, Bing (Archives of Acoustics, 2022)
Cavitation has been widely used in wastewater degradation, material synthesis and biomedical field under dual-frequency acoustic excitation. The applications of cavitation are closely related to the power (i.e. the rate of internal energy accumulation) during bubble collapse. The Keller–Miksis equation considering liquid viscosity, surface tension and liquid compressibility is used to describe the radial motion of the bubble. The model is built in predicting the power during bubble collapse under dual-frequency acoustic excitation. The influences of parameters (i.e. phase difference, frequency difference, and amplitude ratio) on the power are investigated numerically. With the increase of phase difference, the power can be fluctuated in a wide range at all conditions. Three typical characteristics of the power appear under the effects of frequency difference and amplitude ratio. With the increase of amplitude ratio, if the frequency difference is small, the power has two maximum values; and if the frequency difference is medium, there is a maximum value. Otherwise, the power monotonously decreases. The results can provide theoretical references for the selections of experimental parameters of sonoluminescence and sonochemistry in the dual-frequency acoustic field.